Achieving success in nonprofit organizations - Kloppenborg, Timothy J., 1953-; Laning, Laurence J. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
This book is aimed at leaders of nonprofit organizations. These leaders include executive directors, managers, board members, pastors, key volunteers, and anyone who wishes to make a difference. The four overarching areas of living the mission, making good decisions, getting things done,and developing your team emerged from literature searches, focus groups, and surveys to discover objectively what critical skills and knowledge are most useful to leaders of nonprofit organizations. Experts contribute individual chapters in each of these four areas. This book can be used as a reference for specific skills and knowledge in any of these areas. It can also be used as a text since it covers 16 specific chapters within the four major sections and each chapter has a major case example, assessment questions, and summaries of key concepts.
1. Introduction -- Section 1. Living the mission -- 2. Developing and living your mission (Case study: Friars Club) / Len Brzozowski -- 3. Noses in, fingers out: the board's role in achieving success (Case study: Love Your Neighbor Center) / Dick Aft -- 4. Walking the talk: serving stakeholders with ethics, values, and governance (Case study: Talbert House) / Ann Marie Tracey -- 5. Community engagement (Case study: John XXIII Institute) / John Mooney -- Section 2. Making good decisions -- 6. Innovation: creating new products and services (Case study: Support My School) / Rashmi Assudani and Laurence J. Laning -- 7. Making good decisions using data (Case study: United Way of Greater Cincinnati) / Laurence J. Laning -- 8. Portfolio management (Case study: Starfire Council) / Paul Kling -- 9. Leveraging information technology (Case study: Health Collaborative) / Laurence J. Laning -- Section 3. Getting things done -- 10. Financial management (Case study: Buckhorn Children and Family Services) / Phil Glasgo -- 11. Change management (Case study: Xavier University) / Lynda Kilbourne -- 12. Planning and managing projects more effectively (Case study: Mercy Neighborhood Ministries) / Kathryn N. Wells and Timothy J. Kloppenborg -- 13. Sponsoring projects (Case study: Redwood Rehabilitation) / Timothy J. Kloppenborg -- Section 4. Developing your team -- 14. Creating value through human resources (Case study: Xavier University) / Tamara L. Giluk and Shari Mickey-Boggs -- 15. Total quality: integrating customer, employee, and process voices (Case study: Congregation of Saint Joseph) / Timothy J. Kloppenborg -- 16. A strengths based approach for managing your people (Case study: Catholic Strengths and Engagement Community) / Leisa Anslinger and Stephanie Moore -- 17. Creating a sense of employee ownership: lessons from worker-owned cooperatives (Case study: Interfaith Business Builders and Its Cooperatives) / Ray West and Rebecca Luce -- Concluding comments -- Appendix. Our research process -- Index.
Part of: 2014 digital library.
Includes bibliographical references and index.
Title from PDF title page (viewed on March 9, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Nonprofit organizations; nonprofit management; leadership; strategy; execution; portfolio management; project management; information technology; data based decision making; executive leadership; executive sponsorship; organization assessment; Electronic books